2012
DOI: 10.3390/rs4103168
|View full text |Cite
|
Sign up to set email alerts
|

A New Window-Based Program for Quality Control of GPS Sensing Data

Abstract: Abstract:The main purpose of this study is to develop a new Windows-based program that calculates a quality control parameter that shows the quality of Global Positioning System (GPS) observations using GPS data in a Receiver INdependent Exchange (RINEX) format. This new program, Global Positioning System Quality Control (GPSQC), allows general GPS users to easily and intuitively check the quality of GPS observations before post-processing, which will lead to the improvement of GPS positioning precision in div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Several authors have reported that habitat characteristics, such as topography and tree canopy, may significantly reduce location acquisition [41,42]. Nonetheless, GPS error is a systematic error, which can be computed with many methods or mitigated by some augmented methods, such as ground enhancement signal networks or satellite enhancement networks [43]. In this experiment, although “dehesas” can have a dense tree canopy, most missing location fixes were not due to GPS failures, but to the lack of Sigfox coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that habitat characteristics, such as topography and tree canopy, may significantly reduce location acquisition [41,42]. Nonetheless, GPS error is a systematic error, which can be computed with many methods or mitigated by some augmented methods, such as ground enhancement signal networks or satellite enhancement networks [43]. In this experiment, although “dehesas” can have a dense tree canopy, most missing location fixes were not due to GPS failures, but to the lack of Sigfox coverage.…”
Section: Discussionmentioning
confidence: 99%
“…However, because there is currently no common standard for quality check indicators, the method proposed by Dongha Lee (Lee et al, 2012) was used in this study to propose standards and percentages of quality control parameters to provide the initial standards. When evaluating the results of the quality check, the percentage of all observations in the RINEX le that are within the standard range of the total number of observations is calculated.…”
Section: Testing Of Pyrinexmentioning
confidence: 99%
“…Examples of such tools include a MATLAB pro-gram to process TEQC output and obtain more detailed reports of multipath effects (Ogaja and Hedfors, 2007), and a C/C + + program that provides in-creased exibility for viewing and printing TEQC plot les (Hilla, 2002). Some newer programs, such as GPSQC (Lee et al, 2012)d Nut/Anubis (Va-clavovic and Dousa, 2016), focus on quality control and multi-GNSS data monitoring, but they also lack data cleaning and RINEX le editing capabili-ties. This paper introduces PyRINEX, a new multi-purpose Python package for managing and processing GNSS RINEX format.…”
Section: Introductionmentioning
confidence: 99%
“…In our scheme, the reader location is achieved by the GNSS receiver mounted on the reader. Although the GNSS receiver is of low accuracy and the GNSS signal is weak in high building-density areas, the GNSS error is a systematic error, which can be computed with many methods or mitigated by some augmented methods such as ground enhancement signal networks or satellite enhancement networks [33,34]. Therefore, in our scheme, GNSS devices are adopted as the reader locations, which largely reduces the total cost.…”
Section: Tag-location Principlementioning
confidence: 99%